Lack of structural variation but extensive length polymorphisms and heteroplasmic length variations in the mitochondrial DNA control region of highly inbred Crested Ibis, Nipponia nippon - Xue-Lian He; Chang-Qing Ding; Han Jianlin (Public Library of Science, 2013)
The animal mitochondrial DNA (mtDNA) length polymorphism and heteroplasmy are accepted to be universal. Here we report the lack of structural variation but the presence of length polymorphism as well as heteroplasmy in mtDNA control region of an endangered avian species – the Crested Ibis (Nipponia nippon). The complete control region was directly sequenced while the distribution pattern and inheritance of the length variations were examined using both direct sequencing and genotyping of the PCR fragments from captive birds with pedigrees, wild birds and a historical specimen. Our results demonstrated that there was no structural variation in the control region, however, different numbers of short tandem repeats with an identical motif of CA3CA2CA3 at the 3′-end of the control region determined the length polymorphisms among and heteroplasmy within individual birds. There were one to three predominant fragments in every bird; nevertheless multiple minor fragments coexist in all birds. These extremely high polymorphisms were suggested to have derived from the ‘replication slippage’ of a perfect microsatellite evolution following the step-wise mutational model. The patterns of heteroplasmy were found to be shifted between generations and among siblings but rather stable between blood and feather samples. This study provides the first evidence of a very extensive mtDNA length polymorphism and heteroplasmy in the highly inbred Crested Ibis which carries an mtDNA genome lack of structural genetic diversity. The analysis of pedigreed samples also sheds light on the transmission of mtDNA length heteroplasmy in birds following the genetic bottleneck theory. Further research focusing on the generation and transmission of particular mtDNA heteroplasmy patterns in single germ line of Crested Ibis is encouraged by this study.